2016
DOI: 10.5194/tc-10-159-2016
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic mass balance record with rigorous uncertainty estimates deduced from aerial photographs and lidar data – Case study from Drangajökull ice cap, NW Iceland

Abstract: Abstract. In this paper we describe how recent high-resolution digital elevation models (DEMs) can be used to extract glacier surface DEMs from old aerial photographs and to evaluate the uncertainty of the mass balance record derived from the DEMs. We present a case study for Drangajökull ice cap, NW Iceland. This ice cap covered an area of 144 km2 when it was surveyed with airborne lidar in 2011. Aerial photographs spanning all or most of the ice cap are available from survey flights in 1946, 1960, 1975, 1985… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(101 citation statements)
references
References 40 publications
6
94
1
Order By: Relevance
“…The standard deviation is a possible measure of uncertainty (Höhle and Höhle, ). These simple statistics are conservative estimates of the uncertainty (Magnússon et al, ), but are sufficient for our purpose as we do not want to assess the elevation changes in detail but rather to obtain a reasonable limit of detection as additional information for interpretation of the characteristics and changes of the ice‐debris landforms.…”
Section: Methodsmentioning
confidence: 99%
“…The standard deviation is a possible measure of uncertainty (Höhle and Höhle, ). These simple statistics are conservative estimates of the uncertainty (Magnússon et al, ), but are sufficient for our purpose as we do not want to assess the elevation changes in detail but rather to obtain a reasonable limit of detection as additional information for interpretation of the characteristics and changes of the ice‐debris landforms.…”
Section: Methodsmentioning
confidence: 99%
“…The stochastic error was based on the standard error and the mean elevation difference on stable terrain. Magnusson et al (2016) showed how standard methods for quantifying DEM differencing uncertainties neglect the spatial dependence of DEM errors, and as such typically overestimate uncertainties. It should therefore be noted that our uncertainty analysis is conservative.…”
Section: Analytical Uncertaintiesmentioning
confidence: 99%
“…The uncertainty of the elevation difference between the two DEMs is assessed from the statistical distribution of the elevation differences over stable terrain (Magnússon et al, 2016;Rolstad et al, 2009). The standard deviation of elevation differences on stable ground (σ STABLE ) is 3.6 m. The decorrelation length estimated from the semivariogram is approximately 50 m, which gives 604 independent pixels for the entire debris-covered tongue (n GLA ), 330 independent pixels for the debris-covered tongue common with the photogrammetric survey (n GLA_COM ), and 668 independent pixels on the stable zone (n STABLE ).…”
Section: Unmanned Aerial Vehicle Surveymentioning
confidence: 99%